Inside Cover: Direct Dynamic Evidence of Charge Separation in a Dye‐Sensitized Solar Cell Obtained under Operando Conditions by Raman Spectroscopy (Angew. Chem. Int. Ed. 27/2020). Issue 27 (14th May 2020) - Mao, Zhu; Ye, Yutong; Lv, Haiming; Han, Xiao Xia; Park, Yeonju; Zang, Libin; Zhao, Bing; Jung, Young Mee
Abstract : Operando resonance Raman (RR) spectroscopy was used by Z. Mao, B. Zhao, Y. M. Jung, and co‐workers in their Communication on page 10780 for noninvasive and nondestructive microscopic investigations of dynamic interface evolutions in dye‐sensitized solar cells (DSCs) under operando conditions. The creation of new species was observed, and interactions between charge separation pathways and molecular vibrations were studied. Operando RR spectroscopy can also be used to quickly evaluate the performance of DSCs.